The assumption of risk in team sports: A brief critical reflection in light of criminal and civil law (De Legibus - Law Journal, 2024)
Does sport go beyond the rules? Or are these mere general guidelines capable of being implemented through a criterion of social adequacy of concrete conduct? The idea that sporting activity should not go beyond the sporting disciplinary framework is often defended. An injury to physical integrity arising from a violation of a sporting rule results in the illicit conduct and civil liability of the athlete. However, it is necessary to balance, on the one hand, the legal interest in protecting the athlete's physical integrity, preventing the instrumentalization of sport to attack the opponent's person with, on the other hand, the right to sport, which encourages the effort of the athlete for obtaining the result, which means that in a sport that involves physical contact, bodily injuries are frequent. This dichotomy pushes us into a legal limbo where it may not seem clear which cause of justification is most appropriate for granting treatment to such occurrences and, on a second level, which conducts should be considered lawful and which should generate civil liability. of the offending athlete. The right must protect the physical integrity of the athlete, but without harming the normal course of the respective sport.
Keywords: Consent, assumption of sporting risk, sporting rules, sports 'against each other,' ethical-sporting principles, constitutive skills, restorative skills